Q: What is 2x 64?

Write your answer...

Submit

Related questions

It is an expression that can be simplified to: 4x-64

32. 2x=64 can be written as x = 64/2. 64/2=32

-62

2X + 8^2 = 2X+64, for whatever value X. If the question is (2x+8)², the answer is 4x²+32x+64 The formula is (a+b)² = a² + 2ab + b². a=2x, b=8, a²=4x², b²=64

find x when, 2x=128 2x=128 /2 /2 x=128 /2 x=64 then check your answer by doing the following if x=64, then what is 2x? 2(64)=? or 2 * 64=? or 2 x 64=? 2 times 64 equals 128!

66

3x+1+2x-2 = 64 3x+2x = 64-1+2 5x = 65 x = 13

The answer is 32.

66

2x+63=191 2x = 128 x = 64

648 x 84x2 4x22x2x 2x 2x2

Let the length be 2x+8 and the width be x: 2(2x+8+x) = 64 4x+16+2x = 64 6x = 64-16 6x = 48 x = 8 Therefore: length = 24m and width = 8m

x2 - 2x + 65 = 0 Subtract 64 from each side: x2 - 2x + 1 = -64 (x - 1)2 = (i*8)2 where i is the imaginary square root of -1 x - 1 = +/- 8i x = 1 +/- 8i

(x - 2)(x + 2)(x2 - 2x + 4)(x2 + 2x + 4)

Two to the sixth power. 8 with an exponent of 2 equals 64 and 4 with an exponent of 3 equals 64

If: 10x2-64 = 36+6x2 Then: 4x2-100 = 0 And: (2x-10)(2x+10) = 0 So: x = 5 or x = -5

X equals to 8

-64 : 2x(-16) = 2

Solve by the substitution method the given system of the linear equations of 3 variables.2x + 7z = 648y + 6z = 403x - 2y + 4z = 46 (add the first equation with the second equation)2x + 8y + 13z = 1043x - 2y + 4z = 46 (multiply the second equation by 4)2x + 8y + 13z = 10412x - 8y + 16z = 184 (add both equations)14x + 29z = 28814x + 29z = 2882x + 7z = 64 (multiply the second equation by -7)14x + 29z = 288-14x - 49z = -448 (add both equations)-20z = -160 (divide both sides by -20)z = 82x + 7z = 64 (substitute 8 for z)2x + 7(8) = 642x + 56 = 64 (subtract 56 to both sides)2x = 8(divide by 2 to both sides)x = 48y + 6z = 40 (substitute 8 for z)8y + 6(8) = 408y + 48 = 40 (subtract 48 to both sides)8y = -8 (divide by 8 to both sides)y= -1Thus, the solutions are x = 4, y = -1, and z = 8.

53,11 x+y=64 x-y=42 combine terms 2x=106 x=53 substitute x and solve for y 53+y=64 y=11

It is 2x+(-2x) = 0

(64/125)2x-8=(25/16)xOk, you first want to give them common bases:(43/53)2x-8=(52/42)xSo because of the rule (xm)n=xmn, we can say:(4/5)3(2x-8)=(5/4)2xBut you see that we still don't have the same bases, so in order to make them the same, we have to flip either one to make them equal. When you want to flip a fraction, you invert it by putting it to a power of -1.(4/5)3(2x-8)=(4/5)-2xNow, you can ignore the bases and set the exponents equal to each other.3(2x-8)=-2xAnd solve for x:6x-24=-2x-24=-8xx=3

2X * 2X * 2X = 8X^3 2X^3 is saying 2*( X * X * X) = 2X^3

2x * 2x (2*2=4) therefore, 2x*2x equals 4x2.

If RS = 23-2x, ST = 9x -5, and RT = 39, find RS.